The terrestrial malacofauna of Eastern Algeria during the Upper Capsian: The case of Medjez I (El Eulma). (April 2023) - Saafi, Ismail; Merzoug, Souhila; Aouimeur, Samia; Eddargach, Wassel; Mameri, Massipsa
Highlights: A non-essential role in the diet of Medjez I populations. Traces of burning and regular perforations confirm human intervention (consumption). The diversity of techniques and perforating tools in the extraction of the snail's body from its shell. The piercing of terrestrial shells could play other roles (e.g. production of necklaces). Varied collection periods according to species abundance. Abstract: The rammadiya of Medjez I, located near El Eulma (eastern Algeria), is one of the best known sites of the Upper Capsian. The discovered terrestrial malacofauna comes from two excavations (2013 and 2017). The majority of the shells belong to two species: Helix melanostoma and Xerosecta sp. (more than 90% of the total malacofauna). The high proportion of young individuals of Xerosecta sp ., the small size of its shell and the presence of faunal remains highlight the negligible - secondary or complementary - role of the terrestrial malacofauna in the diet of the occupants of Medjez I. The molluscs could be cooked on heated stones, a technique that will preserve the structure of the shell. The presence of systematic (or regular) anthropogenic perforations is due, for a large part, to the methods of extraction of the animal from its shell for consumption: piercing by human canines and/or by a flint or bone tool. However, certain types of perforation, located just behind the peristome at the level of the last whorl of the shell, could have had the objective of manufacturing collars or other ornamental objects. The collection season for the land snail species identified in the site could have taken place during several periods of the year depending on the adaptation of each species to climate change.